PERSEPSI PELANGGAN TERHADAP PELAYANAN SALON KECANTIKAN DI KOTA PADANG PANJANG - Julianti, Tika; Rostamailis, Rostamailis; Rahmiati, Rahmiati (Journal of Home Economics and Tourism, 2015)
The high customer interest forenjoy the beauty salon services in West Sumatra city ofPadang Panjang with no as indicated quality of services provided to customers , sothe performance problems still appears onmany beauty salons. This study aimed todescribe the quality of service at a beauty salon in the city of Padang Panjangseen from the indicator (1) tangibles, (2) reliability, (3) responsiveness, (4)assurance, (5) empathy. This research is a descriptive study. The studypopulation was a beauty salon customer from 4 beauty salon in the city ofPadang Panjang, amounting to 60 people. The sampling technique is nonprobabilitysampling, by using incidental sampling. Collecting data using aquestionnaire based on Likert Scale which has proven its validity andreliability. The study states that the average level of achievement of therespondents customer’s perception regarding the indicators of tangibles 64%unfavorable category, indicators of reliability 81% good category, indicatorresponsiveness 70% moderate category, indicators assurance 60% unfavorablecategory, and the percentage indicator of empathy 62% unfavorable category.Overall assessment based on an average of five indicators, it is known that thequality of service beauty salon in the city of Padang Panjang still in middlecategory with a percentage of 66.34%.Kata kunci: Persepsi pelanggan, kualitas pelayanan.